The Study on Health Impact of Suteti Among Community Living Under Suteti Towers, 2007 - Corrie Wawolumaya (Fakultas Kedokteran Universitas Gadjah Mada, 2007)
Background and Method: A study on the health impact of the Extra High Voltage Transmission power line, 500 kV (SUTETI) was carried out among 1750 people who have been living for more than 15 years around the tower in Jakarta and Tambun. The dependent variables were health impact based on identification of laboratory exams on blood chemistry, electrocardiogram, adult roentgen photo, bone photo roentgen of children, hypertension as well as mental emotional disorders using Cornell Medical Index (CMI) and Sleeping Disorders. The melatonin enzyme was measured trying to identify the association with electromagnetic field exposure and mental psychosomatics evidence. The independent or risk factors measured besides the socio demographic, duration of stay, length of stay at home, smoking were the respondents' annoyance and satisfaction living around the tower and the reasons of feeling not safe. At the same time the electromagnetic field was also measured separately. The personal electric and magnetic field doses were the function of length of stay inside the house and the electric field and magnetic field measured inside the house. The study location was divided into three zones, zone 1, 0-30 ms left and right sides from center of tower foot, zone 2, 30-70 ms and zone 3, 70-100 ms.Results and Conclusion: Study results reported the range of electric field measured , at one meter from the ground, showed the highest 3,2 kV/m just underneath the tower (10-30 m), declined to 0,5 kV/m about 70 m away from the center of the tower and steadily declined, about 70-100 m, the electric field became very small to 0,0 kV/m The magnetic field measured were, the highest 20-30 m, 534 mA/m ( 6,7x 10 -² mT), declined at the distance of 70 m to 110 mA/m ( 1,3 x 10 -² mT ), very small at a 100 m, 50 mA/m ( 6,3 x 10 -3 mT). Study results also revealed that there were no significant associations identified between adults roentgen results, children bone roentgen results, hypertension, mental emotional disorders/ CMI, sleeping disorders with electric and magnetic field dose . The logistic regression functions reported the magnetic field dose as a borderline determinant to electrocardiogram. People who lived 0-70 m had 7 times greater risk to suffer from emotional mental disorders than those living >70 m away from the tower even though mental emotional disorders was neither significant to electro field dose nor to magnetic field dose. The melatonin correlates positively with electromagnetic doses which mean melatonin was not suppressed by the electromagnetic exposures. Melatonin also neither associated with CMI nor with sleeping disorders.Keywords: Extra High Voltage Power Line Transmission (SUTETI), lab exams on blood chemistry, electrocardiogram /ECG, roentgen, bone roentgen in children, CMI, Sleeping disorders, melatonin, electric field dose, magnetic field dose